Observer Design Method for Discrete-Time Lpv Descriptor Systems - Chavez-Orostica, H; Acosta-Barbosa, K; El Aiss-Berazouq, H (Institute of Electrical and Electronics Engineers Inc., 2021)
This paper deals with observer design for the class of discrete time-varying descriptor systems. In particular, it is assumed that the dynamical system matrix is a function of time-varying parameters that are not precisely known. For this class of system, a Linear Matrix Inequality (LMI) based approach is proposed to the design of complete state observers. An affine parameter-dependent Lyapunov function is considered in order to ensure the error convergence between the actual and estimated state. A numerical example is presented in order to show the proposed observer performance. © 2021 IEEE.